(untitled) (Research, Society and Development, 2024)
Hodgkin’s lymphoma (HL), a cancer derived from mature B cells, is one of the most common lymphomas, which, according to the results of Freitas’ study, mainly affects the active population of society. In the Northeast region of Brazil, HL is considered the fourteenth most prevalent type of cancer affecting men and the seventeenth most prevalent in women. The objective of this work is to analyze the epidemiological profile of Hodgkin’s disease from 2012 to September 2023. Methodology: This is an epidemiological study carried out based on data from the health information department of the SUS (Sistema Único de Saúde). The variables used were: hospital admissions, deaths, age group, color/race, sex, hospital expenses and health macro-region. Results: the region with the highest number of hospitalizations, hospital expenses, hospital deaths, this study showed that it was the Southeast region, however the average number of days of hospitalization is higher in the North region. Males are more affected and the most prevalent age group is 30 to 39 years old. Conclusion: This disease of the lymphatic system is of great importance and causes physical, social and emotional damage. Therefore, more studies are needed for early diagnosis, advances for treatments to be more effective to reduce the number of people affected, increase the chances of a cure and reduce public spending.